Pemikiran Politik K.H. Abdulloh Suyuthi Bogangin Mursyid Tarekat Sadziliyyah Bogangin Sumpyuh Banyumas - Muhaini, Akhmad; Muhajir, Muhajir (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This research discusses the political thought of K.H. Abdulloh Suyuthi Bogangin, a murshid of the Sadziliyyah order, who once stated, “I want to be president so that I have the authority to sentence people to death.” This statement is interesting to study in the context of Islamic political thought and Sufi spirituality. The research problem lies in the meaning of the statement, its relation to the values of the Tariqah, and its views on social justice and political authority. This study aims to explore the political ideas of K.H. Abdulloh Suyuthi, understand his perspective on power, and the implications of his statement for the empowerment of the people. The method used is qualitative with historical and hermeneutic approaches. Data were collected through in-depth interviews, literature studies, and document analysis related to his thoughts and activities. The results showed that the statement was not merely an ambition for power, but rather a spiritual reflection on the importance of upholding justice with political power. As a murshid, K.H. Abdulloh views that leadership must be oriented towards divine truth and the welfare of society. This research contributes to the study of Sufism-based Islamic political thought.